1997
DOI: 10.1086/513991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MultiplePlasmodium falciparumInfections in Tanzanian Children during the Phase III Trial of the Malaria Vaccine SPf66

Abstract: In the first phase III efficacy trial of the malaria vaccine SPf66 in Africa, MOIs in SPf66- and placebo-vaccinated children were analyzed by polymerase chain reaction-restriction fragment length polymorphism of the Plasmodium falciparum merozoite surface antigen 2 (MSA2). MOIs were significantly reduced in asymptomatic vaccine recipients compared with those in asymptomatic placebo recipients; however, no differences were observed among symptomatic children in the vaccine and control groups. These results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
1
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 10 publications
6
94
1
5
Order By: Relevance
“…A recent study reported an EIR of as low as 29 (95% CI 19-44) bites per annum (Drakeley et al, 2003). As a consequence of the lower transmission rate our study had less power than expected and even the oldest children in our study had experienced much less P. falciparum exposure than those children elsewhere in whom multiple infections appeared to be protective (Al Yaman et al, 1997a;Beck et al, 1997;Contamin et al, 1996;Farnert et al, 1999;Robert et al, 1996). The mean multiplicity in our study was lower than in most of these studies.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…A recent study reported an EIR of as low as 29 (95% CI 19-44) bites per annum (Drakeley et al, 2003). As a consequence of the lower transmission rate our study had less power than expected and even the oldest children in our study had experienced much less P. falciparum exposure than those children elsewhere in whom multiple infections appeared to be protective (Al Yaman et al, 1997a;Beck et al, 1997;Contamin et al, 1996;Farnert et al, 1999;Robert et al, 1996). The mean multiplicity in our study was lower than in most of these studies.…”
Section: Discussioncontrasting
confidence: 75%
“…In areas of high endemicity, multiplicity depends on the age of the host (Ntoumi et al, 1995;Smith et al, 1999a) and on the transmission intensity (Arnot, 1998). In Idete, Tanzania, mean MOI in asymptomatic children aged 3-7 years was five infections per carrier (Beck et al, 1997). In contrast, in children aged less than one year in the same village, mean multiplicity was only two infections per child .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…falciparum. Even in areas of the highest endemicity, the build up of overall clinical immunity takes several years, whilst multiple infections can be ac-quired rapidly even after effective antimalarial treatment (BECK et al, 1997). The immunity associated with coinfecting parasites seems to be an important component of the overall battery of protective responses available to the partially immune host.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found differences between the parasitological picture in children with asymptomaticP falciparum infections and that in clinical malaria patients from the same highly endemic areas (ENGELBRECHT et al, 1995;CONTAMIN et al, 1996;BECK et al, 1997). Surprisingly, instead of a raised frequency of multiple infections during clinical episodes, these studies have all found the converse.…”
Section: Introductionmentioning
confidence: 94%